2016
DOI: 10.1016/j.jval.2016.09.2280
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and Alternative Medicine use and Its Association with Quality of Life Among Cancer Patients Receiving Chemotherapy in Ethiopia: A Cross Sectional Study

Abstract: Background. Today, complementary and alternative medicine (CAM) use is being routinely practiced by cancer patients worldwide. This study aimed at examining the prevalence of CAM use in patients with cancer and comparing the quality of life (QoL) in CAM users and nonusers. Methods. A cross-sectional study was employed on 195 cancer patients receiving chemotherapy at Gondar University Referral Hospital (GURH) chemotherapy center. Interviewer-administered questionnaires were used and the collected data were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 31 publications
5
23
0
Order By: Relevance
“…A recent systematic review on the use of traditional, complementary and alternative medicine in sub‐Saharan Africa showed that T&CM use by patients with cancer ranged from 34.5% to 79% (James, Wardle, Steel, & Adams, ). Use was highest in Ethiopia (Erku, ; James et al, ). It is, therefore, important that healthcare professionals be aware of the high prevalence and the likelihood of persistence of use of T&CM by patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review on the use of traditional, complementary and alternative medicine in sub‐Saharan Africa showed that T&CM use by patients with cancer ranged from 34.5% to 79% (James, Wardle, Steel, & Adams, ). Use was highest in Ethiopia (Erku, ; James et al, ). It is, therefore, important that healthcare professionals be aware of the high prevalence and the likelihood of persistence of use of T&CM by patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In Iran, 219 of 625 patients with cancer (35%) reported use of T&CM (Montazeri, Sajadian, Ebrahimi, Haghighat, & Harirchi, ). Use of T&CM by patients with cancer is high in sub‐Saharan Africa: 34.5%–65% of patients with cancer in Nigeria reported use of T&CM, while up to 73.5% and 79.0% used T&CM in Ghana and Ethiopia respectively (Asuzu et al, ; Erku, ; Ezeome & Anarado, ; Yarney et al, ). In East Africa, up to 70% of the population in general first consult with traditional healers before visiting biomedical facilities (Maurice, ).…”
Section: Introductionmentioning
confidence: 99%
“…Erku found in the study in which he evaluated the use of TCM and its effect on the quality of life in cancer patients receiving chemotherapy that patients using TCM were in the severe stage of cancer. As these patients were also educationally and economically more advanced, it was considered that it was more possible for them to find out TCM practices (16). In our study, there was no correlation between the use of TCM and the stage of cancer.…”
Section: Discussionmentioning
confidence: 47%
“…The second part, which was based on a questionnaire previously developed by Erku, collected information on CAM use. 18 Patients reporting CAM use were asked to provide additional information, such as the type, reasons or motivations for CAM use, consultations with doctors, side effects, 19,20 and perceived effects of CAM use. However, the questionnaire was modified for the purposes of the present study and some new items were added (eg, personal spending on CAM and number of CAMs used).…”
Section: Methodsmentioning
confidence: 99%